Planejamento de montagem de pré-Moldados: análises e sugestão de melhorias - Osada, Danilo Akio Monobi [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
The construction with the use of precast elements can be linked with quick execution, quality control, organization in the productive process, rationalization and reduction of cost. In this work, planning and follow-up items that should be considered when performing a work that uses such a constructive method were researched. In this study, the analyzed data referred to a commercial building carried out with a precast structure in the city of São Paulo, in which difficulties were identified in the planning and execution process, for which improvements were proposed. Factors that were not properly handled for the execution of the work had significant consequences in terms of service and productivity. A basic checklist was developed for items that must be analyzed before and during the assembly of the pieces, based on the parameters mentioned in the literature on the subject and on those that had a negative impact on the schedule in the construction studied

A construção com a utilização de elementos pré-moldados está conectada com rapidez na execução, controle de qualidade, organização no processo produtivo, racionalização e redução de custo. Neste trabalho pesquisou-se itens de planejamento e acompanhamento que devem ser levados em consideração quando realizada uma obra que utiliza tal método construtivo. Para o estudo foram analisados dados referentes a uma obra de edificação comercial realizada com estrutura pré-moldada na cidade de São Paulo, na qual foram identificados dificuldades no processo de planejamento e execução, para os quais foram propostas melhorias. Fatores que não foram devidamente tratados para a execução da obra tiveram consequências significativas no prazo do serviço e na produtividade. Elaborou-se uma lista de checagem básica (checklist) de itens que devem ser analisados previamente e durante a montagem das peças, com base nos parâmetros citados pela literatura referente ao tema e naqueles que tiveram um impacto negativo no cronograma na obra estudada
Precast mounting planning: analysis and suggestion for improvements
Keywords: Construção modular; Indústria de construção civil; Controle de qualidade; Construction industry